Estimation of future carbon budget with climate change and reforestation scenario in North Korea. Issue 6 (15th September 2016) - Kim, Damin; Lim, Chul-Hee; Song, Cholho; Lee, Woo-Kyun; Piao, Dongfan; Heo, Seongbong; Jeon, Seongwoo
Abstract: In terms of climate change, quantifying carbon budget in forest is critical for managing a role of forest as carbon sink. Deforestation in North Korea has been exacerbating at a noticeable pace and caused to worsen the carbon budget. Under the circumstance, this study aimed to assess the impact of climate change and reforestation on the carbon budget in 2020s and 2050s, using the VISIT (Vegetation Integrative SImulator for Trace gases) model. In order to analyze the impact of reforestation, future land cover maps for the 2020s and 2050s were prepared. Among the deforested areas (2.5 × 10 6 ha) identified by comparing land cover maps for different periods, the potential reforestation areas were selected by a reforestation scenario considering slope, accessibility from residence, and deforestation types. The extracted potential reforestation areas were 1.7 × 10 6 ha and the increased forest area was spatially distributed to each district. The percentage change in carbon budget caused by climate change from the 2000s to 2020s is 67.60% and that from the 2020s to 2050s is 45.98% on average. Based on the future land cover, NEP (net ecosystem production) with reforestation will increase by 18.18% than that without reforestation in the 2050s, which shows the contribution to carbon balance. In connection with this long term projection, it is revealed that the gross fluxes such as photosynthesis and respiration may be impacted more obviously by the climate change, especially global warming, than the net carbon flux because of the offset between the changes in the gross fluxes. It is analyzed that changes in carbon budget are very sensitive to climate changes, while the impact of reforestation is relatively less sensitive. Although it is impossible to significantly improve carbon sequestration by establishing forest in a short-term, reforestation is imperative in a long-term view as it clearly has a potential mechanism to offset emitted carbon.